Effects of orally administered enalapril on blood pressure and hemodynamic response to vasopressors during isoflurane anesthesia in healthy dogs. (September 2016) - Coleman, Amanda E.; Shepard, Molly K.; Schmiedt, Chad W.; Hofmeister, Erik H.; Brown, Scott A.
Abstract: Objective: To examine whether preanesthetic administration of enalapril, compared with placebo, results in a greater decline in blood pressure (BP) or decreased responsiveness of BP to isotonic fluids or vasopressors in healthy dogs during isoflurane anesthesia. Study design: Randomized, experimental, placebo-controlled, blinded, crossover study. Animals: Twelve healthy, female, purpose-bred beagles. Methods: Dogs underwent the following week-long treatment protocols, each preceded by a 1 week washout period: oral placebo twice daily (PLA); oral enalapril, 0.5 mg kg −1 twice daily, with the 15th dose withheld on the day of anesthesia (ENA-W), and oral enalapril, 0.5 mg kg −1 twice daily, with the 15th dose administered 90 minutes prior to anesthetic induction (ENA). On day 8 of each treatment period, dogs were anesthetized in random order utilizing a standard protocol. Following stabilization at an end-tidal isoflurane concentration (Fe ′Iso) of 1.3%, invasively measured systolic (SAP), diastolic (DAP) and mean (MAP) arterial blood pressure were continuously recorded via telemetry. Hypotension (SAP < 85 mmHg) was treated with the following sequential interventions: lactated Ringer's solution (LRS) bolus (10 mL kg −1 ); repeated LRS bolus; dopamine (7 μg kg −1 min −1 ); and dopamine (10 μg kg −1 min −1 ) first without and then with vasopressin (1 mU kg −1 hour −1 ). Results: Compared with the PLA but not the ENA-W group, the ENA group had significantly lower average SAP, DAP and MAP at anFe ′Iso of 1.3%, spent more minutes in hypotension, and required a greater number of interventions to correct moderate-to-severe mean arterial hypotension. Conclusions: In healthy dogs, enalapril administered 90 minutes prior to isoflurane anesthesia increases the degree of intra-anesthetic hypotension and the number of interventions required to correct moderate-to-severe hypotension. Clinical relevance: Dogs receiving angiotensin-converting enzyme inhibitors on the day of anesthesia may exhibit clinically significant intra-anesthetic hypotension.